2015
DOI: 10.1016/j.jsbmb.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental vitamin D and calcium on normal colon tissue and circulating biomarkers of risk for colorectal neoplasms

Abstract: This brief review, based on an invited presentation at the 17th Workshop on Vitamin D, is to summarize a line of the author’s research that has been directed at the intertwined missions of clarifying and/or developing vitamin D and calcium and as preventive agents against colorectal cancer in humans, understanding the mechanisms by which these agents may reduce risk for the disease, and developing ‘treatable’ biomarkers of risk for colorectal cancer. The biological plausibility and observational and clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 78 publications
7
45
0
1
Order By: Relevance
“…[33][34][35][36] In our previous pilot studies, vitamin D or calcium supplementation alone, but not in combination, had the strongest observed effects on CRC risk biomarkers in the normal colorectal mucosa. 37 As vitamin D promotes calcium absorption in the intestine, 38 Our estimated calcium supplementation effects on CLDN1 and OCLD expression are consistent with findings from at least one previous cancer cell-culture study in which incubation of Caco-2 epithelial cells in a calcium-free solution rapidly decreased transepithelial resistance and increased paracellular permeability, indicating decreased TJ tightness. These effects were reversed by replenishing extracellular calcium.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[33][34][35][36] In our previous pilot studies, vitamin D or calcium supplementation alone, but not in combination, had the strongest observed effects on CRC risk biomarkers in the normal colorectal mucosa. 37 As vitamin D promotes calcium absorption in the intestine, 38 Our estimated calcium supplementation effects on CLDN1 and OCLD expression are consistent with findings from at least one previous cancer cell-culture study in which incubation of Caco-2 epithelial cells in a calcium-free solution rapidly decreased transepithelial resistance and increased paracellular permeability, indicating decreased TJ tightness. These effects were reversed by replenishing extracellular calcium.…”
Section: Discussionsupporting
confidence: 82%
“…A synergistic effect of these two exposures was seen in two large cohort studies however, not in several smaller observational studies . In our previous pilot studies, vitamin D or calcium supplementation alone, but not in combination, had the strongest observed effects on CRC risk biomarkers in the normal colorectal mucosa . As vitamin D promotes calcium absorption in the intestine, it is possible that it decreases luminal calcium concentrations in the colorectum.…”
Section: Discussionmentioning
confidence: 86%
“…Vitamin D has been found to have antitumour effects, suggesting that it might inhibit the progression of rectal cancer 10 , breast cancer 11 , pancreatic cancer 12,13 , head and neck cancers 14 and other cancers. Urashima 15 suggested that the higher the serum level of vitamin D is, the better is the prognosis of rectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…The findings presented here may help explain how an adequate daily intake of calcium contributes to health, despite there being little change in colonic histological features over a widerange of calcium intake amounts [57][58][59][60]. While having an adequate daily intake of calcium is important to health, most individuals are calcium deficient.…”
Section: Discussionmentioning
confidence: 99%